Hemostatic Risk Factors and Arterial Thrombotic Disease - Reiner, Alexander P.; Siscovick, David S.; Rosendaal, Frits R. (Thrombosis and Haemostasis, 2001)
The pathogenesis of arterial thrombotic disease involves multiple genetic and environmental factors related to atherosclerosis and thrombosis. Acute thrombosis at the site of a ruptured, lipid-rich atherosclerotic plaque is the usual precipitating event in the transition from stable or subclinical atherosclerotic disease to acute myocardial infarction (MI), stroke, or peripheral arterial occlusion (1). Pathologic studies of coronary arteries in acute MI suggest that the acute thrombosis likely involves activation of both platelets and the coagulation system.